ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENDUDUK MEMBUANG SAMPAH RUMAH TANGGA KE LINGKUNGAN PESISIR PANTAI KELURAHAN WAIWERANG KOTA KECAMATAN ADONARA TIMUR KABUPATEN FLORES TIMUR - Mustapa, Apriati; Samin, Mikael; Hasan, Muhammad Husain (Jurnal Geografi, 2024)
The aims of research is (1) to find out the factors make residents throw rubbish coastal environment beach Waiwerang city sub,district. East Adonara District, East Flores Regerency. (2) what the types of rubbish which were thorwn away by the society coastal environment beach waiwerang city sub,district, East Adonara dristict, east Flores Regerency, (3) how is the society overcome to rubbish the coastal environment beach. The type of research is quantitative descriptivt and qualitative descriptivt, informant in as many 36 peoples. Data collection technique to use observastion teachnique, Intervieuw, Documentation and thelast conclusion. The research result (1) The Factors influence resident throw rubbish the coastal environment beach Waiwerang city sub.district, East Adonara District, East flores Regerency that is fasilitas and infrastructure cleanliness, not enough awareness throw rubbish on place, the settlement too near to the beach. External factors include, training in rubbish management, defilement potential from the settlement, enforcement of rules /not yet effective. (2) types of rubbish found on the beach Waiwerang city. Sub-district, East Adonara District , East Flores Regerency. Namely : type of organic/ wet, and type of inorganic/ dry. (3) How are society to overcome on the coastal onviroment Waiwerang city sub. District, East Adonara district East Flores Regerency. Namely : by burning it before sea rises to reach the rubbish accumulation site, used mutual cooperation when the sea water recedes as a resultnof rubbish being carned undar cureent of sea high tide , and sececly or created by handicrafts.